Crowdsourced assessment of common genetic contribution to predicting anti-TNF treatment response in rheumatoid arthritis - Solveig K. Sieberts (Nature Portfolio, 2016)
Rheumatoid arthritis patients respond differently to anti-TNF treatment. Using community-based challenge, the authors show that currently available data does not reveal meaningful genetic predictors of response to anti-TNF therapy, thus confirming clinical observations.